1983
DOI: 10.1002/cne.902200402
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of cerebellar mossy fiber synapses in the rat: A quantitative electron microscope study

Abstract: The differentiation of cerebellar glomeruli was investigated by quantitative electron microscopy, starting with the period at which mossy fibers made their first appearance. Two developmental stages could be delineated in the maturation of the mossy fiber-granule cell synapse. 1. A primary growth stage (postnatal days 6--15) characterized by the rapid enlargement of mossy rosettes and the intense proliferation of post-synaptic dendrites. The synaptic perimeter of mossy terminals, i.e. percentage of membrane su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 28 publications
6
128
0
Order By: Relevance
“…This MT regulation might control the MF growth cone enlargement and axon spreading that occurs when they contact GCs in vivo [11]. Crucial in vivo evidence demonstrated that Wnt-7a −/− mice had decreased complexity and synapsin-I levels at glomerular rosettes, consistent with the observation that WNT-7a could induce synapsin-I clustering in cultured MFs [10].…”
Section: Vertebrate Wnts As Retrograde Signals During Synapse Developsupporting
confidence: 62%
See 1 more Smart Citation
“…This MT regulation might control the MF growth cone enlargement and axon spreading that occurs when they contact GCs in vivo [11]. Crucial in vivo evidence demonstrated that Wnt-7a −/− mice had decreased complexity and synapsin-I levels at glomerular rosettes, consistent with the observation that WNT-7a could induce synapsin-I clustering in cultured MFs [10].…”
Section: Vertebrate Wnts As Retrograde Signals During Synapse Developsupporting
confidence: 62%
“…MFs from pontine explants grown in GC-conditioned medium displayed increased axonal area and growth cone size, in addition to complexity, features typically observed after MFs enter the cerebellar cortex and contact GCs [11]. These changes were mimicked by the addition of soluble WNT-7a or the GSK-3β inhibitor lithium chloride (LiCl), and blocked by the Wnt antagonist secreted Frizzled-related protein (sFRP) [10].…”
Section: Vertebrate Wnts As Retrograde Signals During Synapse Developmentioning
confidence: 99%
“…Moreover, the majority of both α1 and α6 subunit proteins accumulated adjacent to the Golgi cell axon terminals. These results demonstrated that (1) GAD-positive growth cones and varicosities probably undergo a change to GABAergic terminals [26,48], (2) GABAergic synapses were massively formed during the second postnatal week [2,28,31,37], and (3) GABAergic innervation might initiate the expression of the GABA A receptor α1 and α6 subunit genes, as well as trafficking and clustering of proteins to the synaptic site [1,8,12,13,16,17,20,24,46,48,61].…”
Section: Formation and Maturation Of Gabaergic Synapses In The Cerebementioning
confidence: 99%
“…Several electron microscopic investigations demonstrated ontogeny of the GABAergic synapses [2,27,28,45]. Sequential to excitatory synapse assembly, inhibitory synapses appear at the end of the first postnatal week and the number of GABAergic synapses increases during the second and third postnatal week in the rat cerebellar granular layer [2,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation